Solid phase microextraction analysis of volatile constituents of heated palm olein and selected oils - Omar, Muhammad Nor; Muhd Nor, Nor Nazuha; Idris, Nor Aini (Oriental Scientific Publishing Co., 2009)
Effect of heating on the development of volatile aroma constituents of palm olein and selected oils was studied. The aroma constituents of heated oils were collected using a solid-phase microextraction (SPME) headspace technique with an adsorbent of a divinylbenzene/carboxen (50/30μm) on polydimethylsiloxane (PDMS) fibre. The extracted volatiles were desorbed from the fibre in the injection port of the gas chromatograph at 250oC and the aroma constituents were identified by GC-MS. The analytical data showed that compounds responsible for the rancidity, i.e hexanal, 2E,4Eheptadienal and 2E,4E-decadienal increased significantly when the oils were heated above 100oC while there were no significant changes in their amounts when heating below 60oC. Meanwhile, the volatile contents were slightly increased when the oils were heated at 80oC. In palm olein, the hexanal content before heating (1.5 μg/g ) was similar with its content (1.6 mg/g) after heating at 60oC. However, when palm olein was heated between 100oC and 180oC the hexanal content increased to 6.4 μg/g and 8.7 mg/g respectively. Similar patterns were also observed when soybean, sunflower and corn oils were heated. In soybean oil, the hexanal content before heating was 3.2 μg/g and rose to 13.2 μg/g after heating at 180oC. The concentration of hexanal in sunflower oil increased from 3.6 μg/g to 12.7 mg/g when the oil was heated at 40oC and 180oC respectively. Meanwhile in corn oil, the hexanal contents before heating and after heating at 180oC were 2.8 μg/g and 13.5 μg/g respectively.